Models of support to family members during the trajectory of cancer: a scoping review protocol. Issue 9 (3rd September 2020) - Samuelsson, Maria; Wennick, Anne; Jakobsson, Jenny; Bengtsson, Mariette
Abstract : Introduction: A cancer diagnose, for example, colorectal cancer, not only affects the cancer-person stricken, but also the surrounding family. Thus, this scoping review intends to identify appropriate models of support that will guide the development of a model of support to family members during the trajectory of colorectal cancer. Methods and analysis: This scoping review will be guided by the methodological framework developed by Arksey and O'Malley, refined by Levac et al and Colquhoun et al, and described by the Joanna Briggs Institute. All the stages will be conducted iteratively and reflexively. First, a search strategy will be developed with a librarian and applied in the following peer-reviewed databases: PubMed, Cumulative Index to Nursing and Allied Health Literature and PsycINFO. Additional searches will be performed in Google Scholar and SwePub for identification of grey literature and hand searched in the reference lists. Searches will be conducted from December 2019 to February 2020. A draft of the preliminary search strategy was performed in PubMed in November 2019. Subsequently, three members of the research team will independently screen all abstracts for relevance, as well as the full-text articles. Studies meeting the inclusion criteria will be critically evaluated using the Joanna Brigg Institute Critical Appraisal Tools. A descriptive summary of study characteristics and of the scoping review process will be presented, including a visual flow diagram. Lastly, a thematic analysis as presented by Braun and Clarke will be conducted. To enhance validity, contact nurses of persons with colorectal cancer will be provided an overview of the preliminary results. Ethics and dissemination: Being a secondary analysis, ethical approval is not needed for this study. The findings of the analysis will be used to inform the design of a future study aiming to develop a model of support and an upcoming scoping review, which will be published in a scientific journal and presented at relevant conferences.